Use of an Isolated Sulfate Reducing Bacterium Desulfuricant Strain for Decomposition of Sulfite - Yan1, Yinan; Zhang1, Jianbin; Zhang1, Yongfeng; Liu1, Zhanying; Bai1, Jie (Asian Journal of Chemistry, 2013)
In this work, the use of a desulfurization strain SRB-1, which isolates from sewage sludge and belongs to the sulfate reducing bacterium (SRB), for the decomposition of sulfite is reported. The strain can utilize sulfite as sulfur source. The strain cells of SRB-1 are motive and Gram negative and belongs to facultative anaerobes. For SRB-1, the optimum growth temperature is determined at 45 ºC, the optimum pH is found at 7.5 and the optimum inoculum concentration is ascertained to 8 %. As a method to eliminate sulfite, the advantages of biological flue gas desulfurization technology are a simple process, low cost and no secondary pollution. These all results suggest that the strain has potential application in the regeneration processes of the industrial solution containing sulfite.